Factors Affecting Firm Value Through Profitability As A Mediation Variable - Julia Jie; Henryanto Wijaya (Graduate Program of Universitas Tarumanagara, 2023)
This study examines the impact of Capital Structure, Firm Size, and Increase in sales on Firm wealth in manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020, with Ability to generate income as an intervening variable. A total of 72 companies were included as a sample in this investigation. The result of this research are capital structure affect firm wealth positively significant, firm size affect firm wealth negatively insignificant, increase in sales affect firm wealth negatively significant, capital structure affect ability to generate effect on ability to generate income, increase in sales affect ability to generate income positively significant, ability to generate income affect firm wealth positively significant, ability to generate income is unable to mediate effect of capital structure and increase in sales on firm wealth, and ability to generate income is able to mediate effect of firm size on firm wealth.